Surviving and thriving in seminary : an academic and spiritual handbook - Zacharias, Danny (H. Daniel) (Lexham Press, 2017)
This book is about getting the most out of seminary. Seminary can be rich and rewarding, but also disorienting. In addition to the typical challenges of doing graduate studies, your experiences in seminary have the potential to affect how you see God, other people, and yourself. The stakes are high, but the good news is that you are not alone! In Surviving and Thriving in Seminary, two experienced professors (and former seminary students) tell you what to expect and how to navigate your years in seminary. They give you advice on how to prepare your own heart and relationships, how to manage your time and energy, and how to acquire the study skills you need. This essential book encourages and equips current and prospective seminary students to get the most out of their time in seminary. - Publisher.